Ionic complex systems based on hyaluronic acid and PEGylated TNF-related apoptosis-inducing ligand for treatment of rheumatoid arthritis - Kim, Yu-Jeong; Chae, Su Young; Jin, Cheng-Hao; Sivasubramanian, M.; Son, Sohee; Choi, Ki Young; Jo, Dong-Gyu; Kim, Kwangmeyung; Kwon, Ick Chan; Lee, Kang Choon; Park, Jae Hyung (ELSEVIER SCI LTD, 2010)
The clinical applications of tumor necrosis factor (TNF)-related apoptosis inducing ligand (TRAIL), an emerging therapeutic protein for cancer and rheumatoid arthritis (RA), are limited by its instability and short biological half-life. In this study, efficient therapeutic modalities for RA treatment were developed in the form of nano-sized complexes (nanocomplexes) based on hyaluronic acid (HA) and polyethylene glycol (PEG)-derivatized TRAIL (PEG-TRAIL) formed by N-terminal specific PEGylation. The nanocomplexes were prepared by simply mixing the positively charged PEG-TRAIL and negatively charged HA, and showed negligible loss of bioactivity compared with the PEG-TRAIL The in vivo biodistribution and diffusion kinetics of Cy5.5-labeled PEG-TRAIL in mice were observed using a near-infrared optical imaging system after subcutaneous injection of three different formulations: PEG-TRAIL in phosphate buffered saline (PBS, pH 7.4), nanocomplex in PBS, or nanocomplex in 1% HA solution. The results suggested that PEG-TRAIL is released slowly in vivo from the nanocomplex in 1% HA. Experiments in a collagen-induced arthritis mouse model demonstrated that the magnitudes of therapeutic effects, as judged by clinical scores and histology, were significantly enhanced by the sustained delivery of PEG-TRAIL, with the order of nanocomplex in 1% HA > nanocomplex in PBS > PEG-TRAIL in PBS. In addition, sustained delivery of PEG-TRAIL from the nanocomplex in 1% HA resulted in significant reduction of serum inflammatory cytokines and collagen-specific antibodies that are responsible for the pathogenesis of RA. These results imply that HA/PEG-TRAIL nanocomplex formulations are promising therapeutic modalities for the treatment of RA. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: TARGETED INDUCTION; DELIVERY SYSTEMS; DRUG-DELIVERY; CANCER-CELLS; TRAIL; RECEPTORS; THERAPY; MICROSPHERES; STABILITY; CYTOKINES